Editorial: actinobacteria in special and extreme habitats: diversity, function roles, and environmental adaptations - Qin, Sheng; Li, Wen-Jun; Dastager, Syed Gulam; Hozzein, Wael N. (Frontiers in Microbiology, 2016)
Keywords: actinobacteria; activities; diversity; environmental adaptation; omics technologies; special and extreme environments

Genetic variability in Indian populations of banana corm weevil [Cosmopolites sordidus (Coleoptera: Curculionidae)] assessed by RAPDs and AFLPs - Yadav, Sweta Kumari U.; Singh, Jyotsna; Padmanaban, B.; Kumar, Lalitha Sunil (International Journal of Tropical Insect Science, 2017)
Cosmopolites sordidus (Germar), commonly known as banana corm weevil, is an important economic pest in Asia that can cause severe yield loss depending upon the stage at which infestation occurs. In spite of its economic importance, little is known about the population structure of this pest in India. Random amplified polymorphic DNA (RAPD) and amplified fragment length polymorphism (AFLP) were used to characterize the population genetic structure of C. sordidus collected from five hot spot locations in India. Nineteen RAPD primers and five selective AFLP primer combinations generated 147 and 304 amplification products, respectively. UPGMA dendrograms generated with both marker systems failed to reveal populations clustered based on geographic distance, which was confirmed by the Mantel test, which did not show a strong correlation between genetic distance and geographic distance. Values of indices of genetic identity showed that the populations were closely related. Though the gene flow estimate (Nm) between the populations was 0.469, suggesting restricted gene flow, the populations are not genetically distinct. These observations suggest that the range expansion of this banana pest in India has taken place through transport of infested corms and plant material, resulting in genetically close populations that are geographically distinct. These results provide important information on the population structure of this pest in India, which will aid in designing suitable strategies for its control and management, especially with respect to insecticide resistance.
Keywords: Aflps; Arbitrary Primers; Bemisia-tabaci; Cosmopolites Sordidus; diversity; Genetic diversity; Germar Coleoptera; insecticide resistance; Markers; Musa Spp.; Pcr; Rapds; Restricted Gene Flow Natural-populations; Scirpophaga-incertulas

Shotgun metagenome guided exploration of anthropogenically driven resistomic hotspots within Lonar soda lake of India - Chakraborty, Jaya; Sapkale, Vibhavari; Rajput, Vinay; Shah, Manan; Kamble, Sanjay; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
Anthropogenic activities mediated antibiotic resistance genes (ARGs) in the pristine aquatic bodies (lakes) is raising concern worldwide. Long read shotgun sequencing was used to assess taxonomic diversity, distribution of ARGs and metal resistance genes (MRGs) and mobile genetic elements (MGEs) in six sites within hypersaline Lonar soda lake (India) prone to various anthropogenic activities. Proteobacteria and Euryarchaeota were dominant phyla under domain Bacteria and Archaea respectively. Higher abundance of Bacteroidetes was pragmatic at sites 18LN5 and 18LN6. Functional analysis indicated 26 broad-spectrum ARGs types, not reported earlier in this ecosystem. Abundant ARG types identified were multidrug efflux, glycopepetide, bacitracin, tetracycline and aminogylcoside resistance. Sites 18LN1 and 18LN5 depicted 167 and 160 different ARGs subtypes respectively and rpoB2, bcrA, tetA(48), mupA, ompR, patA, vanR and multidrug ABC transporter genes were present in all samples. The rpoB2 gene was dominant in 18LN1, whereas bcrA gene in 18LN2-18LN6 sites. Around 24 MRGs types were detected with higher abundance of arsenic in 18LN1 and copper in 18LN2-18LN6, signifying metal contamination linked to MRGs. The bacterial taxa Pseudomonas, Thioalkalivibrio, Burkholderia, Clostridium, Paenibacillus, Bacillus and Streptomyces were significantly associated with ARGs. This study highlights the resistomic hotspots in the lake for deploying policies for conservation efforts.
Keywords: ARGs; diversity; Lonar lake; MGEs; MRGs; Nanopore sequencing

Genetic diversity of toxigenic Fusarium verticillioides associated with maize grains, India - Navale, Vishwambar D.; Sawant, Amol M.; Vamkudoth, Koteswara Rao (Genetics and Molecular Biology, 2023)
In the present investigation, prevalence, genetic diversity, and mycotoxin producing potential of Fusarium species associated with maize grain samples were studied from different geographical regions of India. The highest prevalence of Fusarium verticillioides was recorded as 88.52%, followed by F. coffeatum, F. foetens, and F. euwallaceae, 6.55%, 3.27%, and 1.63%, respectively. We isolated 54 strains of F. verticillioides, and their genetic diversity was studied by inter simple sequence repeats (ISSR). The ISSR fingerprints (AG) 8C and (AG) 8G showed 252 and 368 microsatellite sites in the genome of F. verticillioides and resulted in 99-100% repeatability and reproducibility. The Simpson (SID) and Shannon (H) indices (0.78 and 2.36) suggest that F. verticillioides strains exhibit moderate to high diversity. Molecular detection of fumonisin B1 (FB1) biosynthetic genes (FUM1 and FUM13) involved in FB1 production in F. verticillioides was confirmed by polymerase chain reaction (PCR). Furthermore, 91% of the strains were positive for FB1 production, which was affirmed by liquid chromatography with tandem mass spectrometry (LC-MS-MS). In-vitro appurtenance of F. verticillioides spores exhibited a high to moderate effect on the growth and development of the maize. The current finding demonstrated that most F. verticillioides strains showed a wide range of genetic diversity with varied toxigenic and pathogenic potentials. In conclusion, for the first time, F. coffeatum, F. foetens, and F. euwallaceae species were reported from maize grain samples in India. They were positive for FB1 and negatively affecting grain quality, which is a major concern in food safety.
Keywords: diversity; Food safety; Fusarium verticillioides; Mycotoxin; pathogenicity

Editorial: microbial biodiversity and bioprospecting in polar ecosystems in the genomics era - Rizzo, Carmen; Dastager, Syed Gulam; Ay, Hilal (FRONTIERS IN MICROBIOLOGY, 2024)
Keywords: diversity; FJORD